IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DI SEKOLAH DASARSWASTA ISLAM TERPADU AL-FURQON - Rendi Fiteriadi; Aslan Aslan; Eliyah Eliyah (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The aim of this research is to reveal: 1) The Tahfidz Program Learning System at the Al- Furqon Tebas Integrated Islamic Private Elementary School for the 2023/2024 Academic Year; 2) Teacher Method for Teaching Students to Memorize the Qur'am in the Tahfidz Program at the Al-Furqon Tebas Integrated Islamic Private Elementary School for the 2023/2024 Academic Year. This research uses a qualitative approach and a phenomenological type of research. Data collection techniques used structured interviews, participant observation and documentation. The data analysis techniques used were data reduction, data presentation (display), and drawing conclusions (verification/conclusion drawing). The results of this research show that the Tahfidz Learning Program at Al-Furqon Tebas Integrated Islamic Elementary School for the 2023/2024 Academic Year, namely SDS IT Al-Furqon, implements a holistic approach in the tahfidz program, focusing on memorizing the Qur'an, understanding, recitation, and time discipline. The school's commitment to quality improvement is evident in program development, additional training, and an emphasis on repetition to increase student independence. Time management and collaboration with parents create a conducive learning environment, while regular evaluation through tahfidz exams and Al-Qur'an reading monitors student progress. A supportive environment, including effective communication and integration of religious values, shapes students' character holistically. The student memorization method in the Tahfidz Program at Al-Furqon Tebas Integrated Islamic Elementary School for the 2022/2023 academic year is adopting the wahdah method with a focus on repetition of verses and student motivation, but prioritizing the Sima'I and muroja'ah methods. The school's flexibility in choosing methods reflects adaptability to student characteristics. The integration of the Kitabah and Sima'I methods shows awareness of individual student needs and a holistic approach. Despite the obstacles in implementing the Muraja'ah Method at home, the school's efforts to find solutions and regular evaluation ensure the consistency of the tahfidz program. Awareness of the diversity of learning styles and commitment to continuously improving the quality of learning, creating a successful holistic approach in the tahfidz program at SDS IT Al-Furqon